Effect of sequential embryo transfer on in vitro fertilization and embryo transfer outcomes: a systematic review and meta-analysis - Teng, Wending; Xian, Hong; Wang, Fang; Wang, Yicheng; Meng, Xiangqian; Zhang, Xiaojian; Shan, Xudong; Yi, Jiangying (Frontiers in Medicine, 2023)
BACKGROUND Sequential embryo transfer has been recognized as a strategy to increase pregnancy rates in women undergoing in vitro fertilization and embryo transfer (IVF-ET). However, its impact on assisted reproductive outcomes remains to be substantiated by robust evidence. This systematic review aims to summarize and analyze the available evidence to investigate the effect of sequential embryo transfer on assisted reproductive outcomes.A comprehensive literature search was executed across the Pubmed, Cochrane Library, Web of Science, and Scopus databases in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data were aggregated utilizing a random effects model, and the resultant outcomes were articulated as odds ratios (ORs) along with their 95% confidence intervals (CIs). RESULTS The pooled results revealed a statistically significant enhancement in reproductive outcomes for infertile patients undergoing sequential embryo transfer as evidenced by elevated rates of chemical pregnancy (OR = 1.67, 95% CI = 1.23-2.27), clinical pregnancy (OR = 1.78, 95% CI = 1.43-2.21), and ongoing pregnancy (OR = 1.54, 95% CI = 1.03-2.31). Compared with cleavage-stage embryo transfer, sequential transfer yielded superior outcomes in terms of chemical pregnancy rate (OR = 2.08, 95% CI = 1.35-3.19) and clinical pregnancy rate (OR = 1.78, 95% CI = 1.37-2.31). Furthermore, among the repeated implantation failure (RIF) cohort, sequential embryo transfer surpassed blastocyst-stage transfer, delivering a heightened chemical pregnancy rate (OR = 1.66, 95% CI = 1.19-2.53) and clinical pregnancy rate (OR = 1.65, 95% CI = 1.19-2.27).CONCLUSION Our meta-analysis indicates that sequential transfer may enhance clinical pregnancy rate in a small subgroup of well-selected women. While promising, further evidence from prospective studies is needed.